Penser et concevoir pour le développement du sujet tout au long de la vie : de l’enfant dans sa vie quotidienne à l’adulte en situation de travail - Françoise Decortis; Anne Bationo-Tillon; Lucie Cuvelier (Activités)
This paper draws on research results in child-oriented ergonomics to identify the essential questions and criteria involved in design for human development (Decortis, 2015). Two main theoretical frameworks are applied to study technological artefacts : the instrumental approach (Rabardel, 1995) and the activity cycle of creative imagination (Vygotski, 2010) using the NAM model (Decortis, 2015). Questions are discussed in reference to traditionally studied situations in ergonomics, with the object of gaining a perspective on successful contributions of child-oriented ergonomics in situations of work and professional training.